A educação popular como possibilidade de emancipação para a vida de crianças e adolescentes em situação de vulnerabilidade social - Martins, José Eduardo (Universidade do Vale do Rio dos Sinos, 2018)
This research paper deals with the themes related to the conceptions of education, such as challenges to contemporaneous systems of education, globalization, public socio-political policies, popular education, and social exclusion and or inclusion, whose central focus of investigation is the proposed project of education known as the Popular Education and Social Promotion sponsored by the FOUNDATION FÉ E ALEGRIA, located in the county of Palhoça in the State of Santa Catarina in Brazil. Its main objective is to present a qualitative research which makes use as the basic sources the data collected from the analysis of documents, shared observation, interviews with social workers from the FOUNDATION FÉ E ALEGRIA SC, employed as methodological helpmates to gather insights and selective influx of data and analysis of content. The research is trying to find answers to the problem of how the FOUNDATION FÉ E ALEGRIA SC develops the proposed popular education for children and adolescents coming from families of lower income and in situation of social vulnerability at times of shifts of extra-curricular programs at schools. The main objective is to analyze the proposed program of popular education ministered by the FOUNDATION FÉ E ALEGRIA SC aiming at the creation of an identity conducive to an emancipation of the life of children and adolescents, in a situation of social vulnerability, by transferring to complementary activities of subsidiary nature in between regular programs with the help of social workers (officials, educators, and managers), with a view to drawing up a proposal for permanent training. Among the specific objectives needed to be investigated is the formation of social workers of the FOUNDATION FÉ E ALEGRIA SC, as regards their understanding of popular education by means of a detailed analysis of institutional documents and analyze the texts of the participants of the research (social workers of the FOUNDATION FÉ E ALEGRIA SC) how the project of popular education is being implemented in daily routine. The study drew the conclusion that the educational project of the FOUNDATION FÉ E ALEGRIA SC did in fact achieve forging an identity of emancipation in the life of the children and adolescents who were attended by the institution during the period of complementary educational activity, although fragile. The Institution has been an important area of social protection for children and adolescents in situation of social vulnerability who attend it, preventing them from being exposed to situations of physical and psychological violence if they were on the street or even at home, thus collaborating to guarantee the social rights of this part of the population. The group of educators interviewed, reflecting on their teaching experiences, found that the educational proposal of the Institution is theoretically well elaborated, demonstrated to know the institutional educational proposal, however they point out that conditions are not occurring to practice what is indicated there. As a result, this study proposes the adoption, by the unit of Fé e Alegria SC and others social-educational centers of Fé e Alegria in Brazil of a permanent project of training its social workers in the perspective of Popular Education.
Keywords: Prática Emancipatória; Desigualdade social; Educação popular; Emancipatory Practice; Social inequality; Popular education; ACCNPQ::Ciências Humanas::Educação